Human first, leader second how self-compassion outperforms self-criticism - Backus, Massimo (Ascent Audio, 2024)
So many leadership and compassion books seek to remind leaders to "behave human" and treat those around them with care. But the truth is that leaders are human. They're not playing at being human or calling forth their humanity on demand. Their struggle in marrying leadership and compassion stems from leaders ignoring self-care-the lack of compassion toward their subordinates is just a symptom. Human First, Leader Second introduces leaders to the practice of self-compassion through a six-step framework designed to ease even the most hard-headed and hard-assed leaders into thoughtful and productive introspection: Backward: Biography, Biology, Backstory; Forward: Purpose, Values, Priorities; Inward: Intentions, Feelings, Thoughts; Outward: Intent, Actions, Behaviors; Leeward: Self-care and Personal Accountability; Wayward: Regret and Self-forgiveness. Offering strategies for a personalized exploration of self-compassion-and what works best for the individual-this book will help leaders grow awareness to the importance of self-care while debunking the myth that compassion equals weakness. Regardless of our title or influence, we are all humans first, who need compassion.
Online resource; title from title details screen (O'Reilly, viewed October 22, 2024)
Keywords: Leadership; Self-consciousness (Awareness); Self-actualization (Psychology); Work-life balance; Quality of life; Conscience de soi; Conciliation travail-vie personnelle; Qualité de la vie; quality of life; Audiobooks; Livres audio